Judicial Nature of Evidence in Criminal Proceeding - GMYRKO, Valery P.; SHUMYLO, Mykola Ye.; VAPNIARCHUK, Viacheslav V.; KAPLINA, Oksana V.; SHYBIKO, Vasily P. (Journal of Advanced Research in Law and Economics, 2019)
The urgency of the problem stated in the article is conditioned by the necessity to determine the legal nature of the evidence in criminal proceedings and the evolution of the views of domestic scientists on this legal phenomenon. The purpose of the article is to consider the legal nature of the evidence in criminal proceedings and to determine their legal structure. The main approach to the study of this problem was to conduct a methodological analysis of the phenomena of ‘concept’ and ‘definition’, on the basis of which it was argued that judicial evidence has no essence, and only the function of being a symbolic representative of a certain factum probans (from Latin – something that should be proved). The publication concludes that the evidence in criminal proceedings is the result of human thinking operations and can be represented by the methodological construction ‘composition of criminal-judicial evidence’, which includes regulatory-procedural, knowledge, fact-finding and judicial-interpretation segments. In addition, the opinion expressed the inappropriateness of fixing evidence in the criminal procedural law and proposed a pragmatic approach to this issue, which is in line with current European jurisprudence. The materials of the article represent both theoretical and practical value. They can be used for further scientific investigation of evidence in criminal proceedings, as well as for a proper understanding and enforcement of law enforcement criminal proceedings.